IMPLEMENTASI SISTEM TANGGUNG RENTENG PADA PEMBIAYAAN LAYANAN BERBASIS JAMAAH (LASISMA) DALAM PERSPEKTIF FIQIH MUAMALAH DI BMT NU JAWA TIMUR CABANG CLURING BANYUWANGI - Hikmah Nur Izza; Indana Almas Azhar (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
One of the efforts of BMT NU to prosper the Indonesian economy in the micro-community sphere is by providing assistance in the form of financing Layanan Berbasis Jamaah (LASISMA), the realization of which is without collateral but implementing a system of Tanggung Renteng. jointly in the perspective of Fiqh Muamalah. This research uses a descriptive qualitative approach to the type of field research. The research location is at KSPPS. BMT NU East Java Cluring Banyuwangi Branch. Selection of informants with purposive sampling. Primary and secondary data sources. Data validity with source triangulation. Data analysis with miles and huberman. The results of the Tanggung Renteng system research on LASISMA financing use the kafalah bid-dayn contract which is in accordance with Islamic Civil law, namely Fiqh Muamalah, and the implementation of the Tanggung Renteng system at BMT NU Cluring Branch is applied when there are partners who are late in installments. The conclusion is that the Tanggung Renteng system is applied when there are arrears, as a solution for BMT NU and as a form of ta'awun among fellow members of the LASISMA group.